'It doesn't do the care for you': a qualitative study of health care professionals' perceptions of the benefits and harms of integrated care pathways for end of life care. Issue 9 (14th September 2015) - Sleeman, Katherine E; Koffman, Jonathan; Bristowe, Katherine; Rumble, Caroline; Burman, Rachel; Leonard, Sara; Noble, Jo; Dampier, Odette; Bernal, William; Morgan, Myfanwy; Hopkins, Philip; Prentice, Wendy; et al.
Abstract : Objectives: To understand healthcare professionals' perceptions of the benefits and potential harms of integrated care pathways for end-of-life care, to inform the development of future interventions that aim to improve care of the dying. Design: Qualitative interview study with maximum variation sampling and thematic analysis. Participants: 25 healthcare professionals, including doctors, nurses and allied health professionals, interviewed in 2009. Setting: A 950-bed South London teaching hospital. Results: 4 main themes emerged, each including 2 subthemes. Participants were divided between (1) those who described mainly the benefits of integrated care pathways, and (2) those who talked about potential harms. Benefits focused on processes of care, for example, clearer, consistent and comprehensive actions. The recipients of these benefits were staff members themselves, particularly juniors. For others, this perceived clarity was interpreted as of potential harm to patients, where over-reliance on paperwork lead to prescriptive, less thoughtful care, and an absolution from decision-making. Independent of their effects on patient care, integrated care pathways for dying had (3) a symbolic value: they legitimised death as a potential outcome and were used as a signal that the focus of care had changed. However, (4) a weak infrastructure, including scanty education and training in end-of-life care and a poor evidence base, that appeared to undermine the foundations on which the Liverpool Care Pathway was built. Conclusions: The potential harms of integrated care pathways for the dying identified in this study were reminiscent of criticisms subsequently published by the Neuberger review. These data highlight: (1) the importance of collecting, reporting and using qualitative data when developing and evaluating complex interventions; (2) that comprehensive education and training in palliative care is critical for the success of any new intervention; (3) the need for future interventions to be grounded in patient-centred outcomes, not just processes of care.